Kebijakan arah selatan baru sebagai diplomasi pertahanan Korea Selatan di Kawasan Asia Tenggara: New southern policy as South Korea's defence diplomacy in the Southeast Asia Region - Rahmadanu Pradityo (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
President Moon Jae In announced the New Southern Policy as South Korea's foreign policy in 2017. The policy aims to strengthen the special relationship between South Korea and India and countries in the Southeast Asian region. The New Southern Policy has three pillars (3P) People, Prosperity, and Peace which are the direction of South Korea's foreign policy. In carrying out this policy, South Korea also carries out defense diplomacy through military assistance, sales, and transfer of weapons technology to countries in the Southeast Asian region. This article explains why South Korea uses the New Southern Policy as South Korea's defense diplomacy to Southeast Asian countries through arms sales and transfers. This study uses the velvet challenge framework from Gregory Winger with a qualitative approach and methods of collecting literature study data from books, journals, official government websites, scientific reports/papers, and online news media. The results of this study indicate that South Korea's economic strength through its defense industry has succeeded in introducing weapons products and acquiring new purchasers as indicated by the increasing volume of weapons sales to countries in the Southeast Asian region.